2007
DOI: 10.1128/iai.00948-06
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Nramp1 BB Genotype againstBrucella abortusin the Water Buffalo (Bubalus bubalis)

Abstract: We tested 413 water buffalo cows (142 cases and 271 controls) for the presence of anti-Brucella abortus antibodies (by the skin test, the agglutination test, and the complement fixation test) and the Nramp1 genotype (by capillary electrophoresis). Four alleles (Nramp1A, -B, -C, and -D) were detected in the 3 untranslated region of the Nramp1 gene. The BB genotype was represented among only controls, providing evidence that this genotype confers resistance to Brucella abortus. The monocytes from the BB (resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…The highest gene expression level was recorded in the infected carriers of the (GT) 16 allele. In another study, Capparelli et al (2007a) confirmed that non-infected (GT) 16 monocytes exhibited a basal level of SLC11A1 expression that was approximately five times higher than those of non-infected (GT) 12 monocytes. Moreover, both infected and non-infected (GT) 16 monocytes exhibited significantly higher reactive oxygen intermediate generation than did monocytes from carriers of other alleles.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The highest gene expression level was recorded in the infected carriers of the (GT) 16 allele. In another study, Capparelli et al (2007a) confirmed that non-infected (GT) 16 monocytes exhibited a basal level of SLC11A1 expression that was approximately five times higher than those of non-infected (GT) 12 monocytes. Moreover, both infected and non-infected (GT) 16 monocytes exhibited significantly higher reactive oxygen intermediate generation than did monocytes from carriers of other alleles.…”
Section: Discussionsupporting
confidence: 60%
“…Alleles (GT) 16 and (GT) 12 are present in the first block and correspond to the alleles reported by Capparelli et al (2007a) as B (DQ095781) and A (DQ095780), respectively. The second block present (GT) 14 and (GT) 15 repeats, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown, however, that Nramp1 does not play a prominent role in protecting experimentally infected mice from Brucella infections (33). Studies of ruminants have also shown that the contributions of this divalent cation transporter to host defense against Brucella infections vary depending on the species of ruminant being examined (10,54). Thus, the severe attenuation exhibited by the B. abortus mntH mutant in C57BL/6 mice (which lack a functional Nramp1) (67) and cultivated macrophages obtained from these mice is particularly striking.…”
Section: Discussionmentioning
confidence: 99%
“…and Leishmania sp. (Vidal et al, 1995;Gruenheid et al, 1997;Zwilling et al, 1999;Jabado et al, 2000;Capparelli et al, 2007). The function of Nramp1 in virus infection has not yet been elucidated, but its about 8-fold upregulation in PBLs following CSFV infection indicates that it is possibly involved in the anti-CSFV cellular response.…”
Section: Discussionmentioning
confidence: 99%